2021
DOI: 10.1155/2021/9952701
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Outcomes in Pregnant Women Infected with COVID-19 in Babol, North of Iran: A Retrospective Study with Short-Term Follow-Up

Abstract: During the coronavirus disease 2019 (COVID-19) pandemic, the number of pregnant women and neonates suffering from COVID-19 increased. However, there is a lack of evidence on clinical characteristics and neonatal outcomes in pregnant women with COVID-19. We evaluated short-term outcomes (4 weeks postdischarge) and symptoms in neonates born to mothers infected with COVID-19. In this retrospective cohort study, we included all neonates born to pregnant women with COVID-19 admitted to Ayatollah Rohani Hospital, Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In agreement with the findings of this study, Akbarian-Rad et al (11) reported that all neonates had Apgar scores of 8 or 9 out of 10 in the first and fifth minutes, respectively, and that none of the infants needed to be revived in the delivery room. Newborns weighed ± 697 gram at birth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with the findings of this study, Akbarian-Rad et al (11) reported that all neonates had Apgar scores of 8 or 9 out of 10 in the first and fifth minutes, respectively, and that none of the infants needed to be revived in the delivery room. Newborns weighed ± 697 gram at birth.…”
Section: Discussionsupporting
confidence: 92%
“…In the same line, Akbarian-Rad et al (11) conducted a retrospective cohort research with eight neonates delivered to COVID-19-positive pregnant women who were more than 37 weeks along in the pregnancy to evaluate short-term outcomes and symptoms among neonates of COVID-19 positive moms.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with other studies in the Middle East as well as in other worldwide countries such as the United States ( Hirshberg et al, 2020 ) and China ( Chen H et al, 2020 ). In Iranian pregnant women, the most common reported symptoms of COVID-19 were fever, cough, and dyspnea ( Kazemi Aski et al, 2020 , 2021 ; Motlagh et al, 2020 ; Pirjani et al, 2020 ; Sattari et al, 2020 ; Akbarian-Rad et al, 2021 ; Alipour et al, 2021 ; Samadi et al, 2021 ; Vaezi et al, 2021 ; Vizheh et al, 2021 ; Abedzadeh-Kalahroudi et al, 2021b ). Lymphopenia and elevated C-reactive protein levels ( Pirjani et al, 2020 ; Akbarian-Rad et al, 2021 ; Vaezi et al, 2021 ; Abedzadeh-Kalahroudi et al, 2021a , b ), in addition to Elevated lactate dehydrogenase (LDH; Kazemi Aski et al, 2020 ; Abedzadeh-Kalahroudi et al, 2021a ), were the most common laboratory findings observed.…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
“…In Iranian pregnant women, the most common reported symptoms of COVID-19 were fever, cough, and dyspnea (Kazemi Aski et al, 2020Motlagh et al, 2020;Pirjani et al, 2020;Sattari et al, 2020;Akbarian-Rad et al, 2021;Alipour et al, 2021;Samadi et al, 2021;Vaezi et al, 2021;Vizheh et al, 2021;Abedzadeh-Kalahroudi et al, 2021b). Lymphopenia and elevated C-reactive protein levels (Pirjani et al, 2020;Akbarian-Rad et al, 2021;Vaezi et al, 2021;Abedzadeh-Kalahroudi et al, 2021a,b), in addition to Elevated lactate dehydrogenase (LDH; Kazemi Aski et al, 2020; Abedzadeh-Kalahroudi et al, 2021a), were the most common laboratory findings observed. The SARS-CoV-2 infection in this population presented mainly as a mild-tomoderate disease (Kazemi Aski et al, 2020;Vizheh et al, 2021).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
See 1 more Smart Citation